Digital Transformation in Increasing Business Competitiveness in the Industrial Era 5.0 - Ahmad Yahya Hamiduddin (CV. Civiliza Publishing, 2026)
Digital transformation has become an important strategy for the business world in facing the increasingly complex dynamics of global competition, especially in the industry 5.0 era, which emphasizes a human-centered approach on sustainability, and resilience. This study aims to analyze the role of digital transformation in enhancing business competitiveness in the industry 5.0 Era and to identify the factors that influence the success of its implementation. This research uses a qualitative approach with a literature review method (library research). Data was obtained from various scientific sources in the form of national and international journal articles, academic books, and relevant documents discussing digital transformation, business competitiveness and Industry 5.0. Data was analyzed using content analysis techniques to systematically synthesize concepts, findings, and expert views. The results of the study show that digital transformation plays a significant role in increasing business compaetitiveness through improved operational efficiency, product and service innovation, strengthened customer relationships, and data-driven decision making. The success of digital transformation is influenced by visionary leadership, human resource readiness, an adaptive organizational culture, and technological infrastructure support. From an Industry 5.0 perspective, digital transformation is not only oriented towards efficiency and economic profit, but also towards human values, sustainability, and long-term business resilience. Thus, holistic and human- oriented digital transformation is the key in creating daya saing sustainable business in the Industry 5.0 era.